An experimental analysis of factors underlying neglect in line bisection. - Butter, C M (1988)
The finding that patients with neglect make larger errors when bisecting longer lines could be due to failure to disengage attention from a segment of the line on the ipsilesional side, or to a reduced ability to direct attention and/or action contralaterally. The findings are reported from a patient with left-sided neglect who set the midpoint further away from the right end of lines as their length increased, a finding consistent with the latter interpretation. His errors were significantly related to length and lateral extent of lines presented in left hemispace, but only to length of lines presented in right hemispace.